Redefining sport based on the Russian doping experience - Zelenkova, I.; Pitsiladis, Y.; Badtieva, V.; Pakhnotskaya, M. (Current Sports Medicine Reports, 2019)
The use of prohibited substances remains a global issue as evidenced by recent revelations of the high doping prevalence at the very elite level of sport (1), and is not confined only to Russia. Protection of the clean athlete is a top priority for the International Olympic Committee (IOC) and the World Anti-Doping Agency (WADA). The problem of doping in modern-day sport is exacerbated by the focus on winning at all costs. The winner gets fame, multimillion-dollar contracts, and becomes a role model for young aspiring athletes. For many athletes, especially from developing countries, modern-day sport is a social mobility tool, a means of survival, and a source of income for an extended family. This reality can lead vulnerable athletes to use any possible means to obtain success. The continuous exposure of doping by high-profile athletes serves to perpetuate the stereotype that doping is the only way to achieve sporting success (2-4).